2008
DOI: 10.3748/wjg.14.2844
|View full text |Cite
|
Sign up to set email alerts
|

Laparo-endoscopic “Rendezvous” to treat cholecysto-choledocolithiasis: Effective, safe and simplifies the endoscopist’s work

Abstract: AIM:To investigate our clinical experience with combined laparo-endoscopic Rendezvous (RV) for the treatment of patients affected by gallstones and common bile duct (CBD) stones and especially to study the never evaluated opinion of the endoscopist concerning the difficulty of the intraoperative endoscopic procedure during the RV in comparison with standard endoscopic retrograde cholangio-pancreatography (ERCP). METHODS:Eighty consecutive patients affected by cholecystolithiasis and diagnosed or suspected CBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
1
22
0
5
Order By: Relevance
“…The technique was first described almost 20 years ago [52][53][54] , and hypothetically, it combines many advantages, such as minimal invasiveness and an acceptable learning curve, at the price of some organization troubles between endoscopists, surgeons and operating room personnel [55][56][57] , but is yet to be accepted. A robust review by La Greca et al [58] analyzed data from 27 papers, which included almost 800 patients and compared the RVT to other approaches. This research showed an overall bile duct clearance of 92.3% and few complications (1.6%-6% bleeding from the sphincterotomy and 1.7%-7% pancreatitis).…”
Section: Intraoperative Ercp (With Concomitant Laparoscopic Cholecystmentioning
confidence: 99%
“…The technique was first described almost 20 years ago [52][53][54] , and hypothetically, it combines many advantages, such as minimal invasiveness and an acceptable learning curve, at the price of some organization troubles between endoscopists, surgeons and operating room personnel [55][56][57] , but is yet to be accepted. A robust review by La Greca et al [58] analyzed data from 27 papers, which included almost 800 patients and compared the RVT to other approaches. This research showed an overall bile duct clearance of 92.3% and few complications (1.6%-6% bleeding from the sphincterotomy and 1.7%-7% pancreatitis).…”
Section: Intraoperative Ercp (With Concomitant Laparoscopic Cholecystmentioning
confidence: 99%
“…The use of the rendezvous technique prevents Wirsung opacification using contrast agents, damage and manipulation of the papilla and the use of risky techniques to access the papilla, such as precut sphincterotomies [38]. Trying to resolving biliary lithiasis and choledocholithiasis at the same time prevents post-ERCP acute cholecystitis from appearing when the cholecystectomy is delayed [13].…”
Section: Discussionmentioning
confidence: 99%
“…Use of intraoperative ERCP has slowly increased among the various endoscopy groups, as it combines ease of use in daily clinical practice with a short learning curve, without the high technical requirements for laparoscopic management of the bile duct [13,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard treatment for cholecystolithiasis is laparoscopic cholecystectomy, whereas the gold standard treatment for isolated common bile duct stones is endoscopic clearance 1. The management of patients affected by gallstones complicated by common bile duct (CBD) stones and/or problems at the papilla of Vater is anyway a challenge as there are many available options for treatment, all being effective but which is the best practice is still unknown 2. The gallbladder may have abnormal position, be intrahepatic, have anomalous form, or be duplicated 3.…”
Section: Introductionmentioning
confidence: 99%